Diagnosis and Management of Pneumocystis Carinii Pneumonia (PCP) in HIV Patients at Klungkung Regional Hospital - Wedanta Mahadewi, I Gusti Agung; Putri Purnama Dewi, Ni Made (International Journal of Psychology and Health Science, 2024)
Pneumocystis carinii pneumonia (PCP) is an opportunistic infection caused by the fungus Pneumocystis jerovecii. This condition generally occurs in immunocompromised patients, especially in  HIV patients, if not treated optimally, it can be life threatening. This infection is the most common opportunistic infection in HIV patients, especially in patients with CD4 cells less than 200 cells/ul. The following is a case of PCP in HIV infection at the Klungkung Regional Hospital. Case Report: Patient AMA, 52 years old came with the main complaints of shortness of breath, cough since 1 week, and fever. On examination the patient was conscious (E4V5M6) and appeared moderately ill. Blood pressure 130/80 mmHg, pulse rate 106x/minute. Respiratory rate 24x/minute, axillary temperature 370C with oxygen saturation 95% with oxygen 4 lpm nasal cannula. On physical examination, rhonchi were found in the right and left paracardia. Routine blood examination found Hb 9.2g/dL, WBC 12.62 thousand/, hematocrit 26.3%, platelets 272 thousand/?L. Liver function examination SGOT 80 U/L, SGPT 74 U/L, urea 23mg/dL, creatinine 0.3mg/dL, NT-Pro BNP 4102 pg/mL, HIV test results showed reactive, IGRA negative. Microbiological examination of the sputum showed positive results for yeast cells and gram-negative bacilli. Chest x-ray examination revealed cardiomegaly with a CTR of 60%, showing pulmonary congestion and a pneumonic infiltrate. Thorax CT scan with results showing bronchitis accompanied by pneumonia and specific process, there is a picture of minimal bilateral pleural effusion, cardiomegaly with pulmonary congestion. The patient was given IVFD infusion therapy of NaCl 0.9% 12 tpm, omeprazole 2x40mg, ondancetron 3x4mg nystatin drop 100.00 units 4x1mL, curcuma 2x1, cotrimoxazole 3x 2 forte tablets. N-acetylcystein 3x200mg fluconazole 1x200mg IV, levofloxacin 1x750mg IV, ceftriaxone 1x2gr, nebulizer with a combination of ipratropium bromide 0.5ng and salbutamol 2.5mg every 8 hour, hydrocortisone 2x100mg IV, furosemide 3x20mg IV, spironolactone 1x50mg PO ivabradine 2x 5mg PO. Discussion: Adhesion pneumonsitis in the alveoli is a host inflammatory response that can cause significant damage to the lungs and impaired gas exchange, causing hypoxia and respiratory failure. The definitive diagnosis of PCP is finding the organism in sputum histopathology originating from induction or BAL (Bronchoalveolar Lavage). Even though the patient's symptoms and clinical symptoms were not carried out, it was highly suggestive of PCP, this patient was diagnosed with PCP and given oral or intravenous Trimetroprim-sulfamethoxazole (TMX-SMX) therapy for 21 days to manage PCP. Conclusion: A PCP in HIV case infection in a 52 year old woman at Klungkung Regional Hospital has been reported. The patient was given co-trimoxazole therapy for 21 days as well as treatment for CHF.